2020
DOI: 10.1038/s41366-020-0642-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations between central and general adiposity with albuminuria: observations from 400,000 people in UK Biobank

Abstract: Background Whether measures of central adiposity are more or less strongly associated with risk of albuminuria than body mass index (BMI), and by how much diabetes/levels of glycosylated haemoglobin (HbA1c) explain or modify these associations, is uncertain. Methods Ordinal logistic regression was used to estimate associations between values of central adiposity (waist-to-hip ratio) and, separately, general adiposity (BMI) with categories of urinary albumin-to-creatinine ratio (uACR) in 408,527 UK Biobank pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
(47 reference statements)
1
8
1
Order By: Relevance
“…In contrast, two cross-sectional studies in Chinese and Korea revealed that women with central obesity tended to develop albuminuria but insignificant relationship between albuminuria and obesity in men [ 25 , 26 ]. Our data support that in men, microalbuminuria is the clusters with the components of MetS, especially central obesity more propensity than women, consistent with a finding in 408,527 UK Biobank participants that each 0.06 increase of waist-to-hip ratio was associated with 75% (71–79%) and 40% (38–43%) increases in odds of higher UACR in men and women, respectively [ 27 ]. This suggests that the long-term sequelae of obesity, fat metabolism, and fat deposition may differ between men and women.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, two cross-sectional studies in Chinese and Korea revealed that women with central obesity tended to develop albuminuria but insignificant relationship between albuminuria and obesity in men [ 25 , 26 ]. Our data support that in men, microalbuminuria is the clusters with the components of MetS, especially central obesity more propensity than women, consistent with a finding in 408,527 UK Biobank participants that each 0.06 increase of waist-to-hip ratio was associated with 75% (71–79%) and 40% (38–43%) increases in odds of higher UACR in men and women, respectively [ 27 ]. This suggests that the long-term sequelae of obesity, fat metabolism, and fat deposition may differ between men and women.…”
Section: Discussionsupporting
confidence: 91%
“… 19 In the current study, LAP was proven to be more closely associated with uACR in prediabetes, than WHR and WHtR, and independent of measurement of general adiposity is consistent with previous data. 5 …”
Section: Discussionmentioning
confidence: 99%
“…19 In the current study, LAP was proven to be more closely associated with uACR in prediabetes, than WHR and WHtR, and independent of measurement of general adiposity is consistent with previous data. 5 Prediabetes was described as a precursor of chronic kidney disease, and vice versa, microvascular dysfunction preceded and contributed to hyperglycemia through impairment of insulin-mediated glucose disposal and insulin secretion. [20][21][22] Meanwhile, visceral obesity was also associated with microvascular abnormality, including insulin-induced microvascular dilation and recruitment, impairments in functional capillary density, and endothelium-dependent vasodilation in the absence of general obesity, [23][24][25] supporting the notion that visceral adiposity was an important driver of DKD.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations